Discursos midiáticos na representação dos refugiados venezuelanos desterritorializados no Brasil (2016- 2017), no jornal digital Folha de Boa Vista, Roraima - Gonzalez, Adriana Esperanza Blanco (2024)
This research analyzes the media discourses regarding the representation of displaced Venezuelans in the migratory exodus initiated in 2016, featured in the digital newspaper Folha de Boa Vista, from the state of Roraima. The objective is to study how this communication medium influences the deconstruction and construction of the identity of displaced Venezuelan refugees, built mainly by the interaction between social and cultural factors with the discourses that attempt to represent them and which are often loaded with stigmatizing messages. Thus, this study has a theoretical framework based on perspectives on the construction of the social identity of displaced Venezuelan refugees, and can contribute to a reconceptualization and rereading of the representation given about these new actors in Brazilian society. The methodology is bibliographic and documentary and the work is situated within the framework of qualitative research based on grounded theory and Critical Discourse Analysis, proposed by Van Dijk. Through Critical Discourse Analysis, a corpus of 222 Information items published in 2016 and 2017 was examined. It was identified that the newspaper repeatedly associated Venezuelan refugees with criminality, irregulars, hungry people, prostitution and drug trafficking, representing them as a threat. The study found the use of terms such as “crisis” and “criminality” to describe the situation on the border, reinforcing a negative view. The newspaper relied on political and health authority sources to substantiate this discourse, legitimizing prejudice against refugees. It is concluded that the coverage of the Venezuelan migratory phenomenon by the Folha de Boa Vista Roraima newspaper was not impartial or balanced between 2016-2017. The representation of refugees was based on negative and derogatory images, without counterpoints or adequate contextualization of the Venezuelan crisis. The expansion of research on the role of the media in constructing imaginaries about vulnerable minorities, articulated with public debates, can boost the transformation of widely normalized discriminatory narratives